2009
DOI: 10.2337/dc08-1641
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Abnormal Lipid Profiles and the Relationship With the Development of Microalbuminuria in Adolescents With Type 1 Diabetes

Abstract: OBJECTIVE -To explore the prevalence of lipid abnormalities and their relationship with albumin excretion and microalbuminuria in adolescents with type 1 diabetes.RESEARCH DESIGN AND METHODS -The study population comprised 895 young subjects with type 1 diabetes (490 males); median age at the baseline assessment was 14.5 years (range 10 -21.1), and median diabetes duration was 4.8 years (0.2-17). A total of 2,194 nonfasting blood samples were collected longitudinally for determination of total cholesterol, LDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
82
4
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 23 publications
6
82
4
2
Order By: Relevance
“…Previous studies have shown an association between albumin excretion and lipid parameters, including total cholesterol, LDL cholesterol, and non-HDL cholesterol (25,26). We found that levels of non-HDL cholesterol were significantly increased in subjects with higher ACR.…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies have shown an association between albumin excretion and lipid parameters, including total cholesterol, LDL cholesterol, and non-HDL cholesterol (25,26). We found that levels of non-HDL cholesterol were significantly increased in subjects with higher ACR.…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies have also reported that girls had higher BMI than boys [17,[23][24][25]. Girls reaching puberty earlier than boys may explain the more advanced pubertal stage in the same age group.…”
Section: Discussionmentioning
confidence: 83%
“…Hypercholesterolemia is reported to be more common among diabetic compared to non-diabetic males [34]. Another study determined that girls had higher lipid levels, among which hypercholesterolemia was the most common, and that age, diabetes duration, increased BMI and A 1C levels were associated with lipid anomalies [24,35]. Polak et al investigated abnormal lipid profiles in children with T1D during puberty and described that cholesterol levels were not associated with metabolic control, while triglyceride levels could have a weak correlation with metabolic control [19].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study performed in 895 young subjects with type 1 diabetes, 20.1% had plasma triglycerides above 1.7 mmol/l, 9.6% had LDL-cholesterol above 3.4 mmol/l and 25.9% had non-HDL cholesterol above 3.4 mmol/l (Marcovecchio et al, 2009). It has been shown that abnormal lipid levels, in type 1 diabetes, predict worse cardiovascular outcomes (Soedamah-Muthu et al, 2004).…”
Section: Treated Type 1 Diabetesmentioning
confidence: 99%
“…It has been shown that abnormal lipid levels, in type 1 diabetes, predict worse cardiovascular outcomes (Soedamah-Muthu et al, 2004). HbA1c has been shown to be independently correlated with LDL-cholesterol, non-HDL cholesterol and triglyceride levels, indicating that these disorders were mostly observed in patients with poor glycemic control (Marcovecchio et al, 2009). In a British follow-up study of 229 children with type 1 diabetes, LDL cholesterol and non-HDL cholesterol values increased with duration of diabetes (Edge et al, 2008).…”
Section: Treated Type 1 Diabetesmentioning
confidence: 99%